2022
DOI: 10.54946/wilm.11057
|View full text |Cite
|
Sign up to set email alerts
|

Caplet Pricing with Backward-Looking Rates

Abstract: Colin Turfus considers the Hull-White short rate model and extends the known closed-form pricing kernel to include the integrated short rate as a separate independent variable, applying it to cap/floor pricing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It will be observed that the leading-order contribution (n = 0) is in its functional form identical to the Hull-White kernel of Turfus [2022], with the caveat that the mean reversion function φ r (t, u) is adjusted up (reducing its impact) by inclusion of the smile factor ψ r (t, t 1 ) in (3.7), with no impact from skew. This means that solutions based on our expansion are likely to retain better accuracy even at longer maturities than those of Turfus and Romero-Bermúdez [2021].…”
Section: Proof a Proof Of This Results Is Given Inmentioning
confidence: 97%
See 4 more Smart Citations
“…It will be observed that the leading-order contribution (n = 0) is in its functional form identical to the Hull-White kernel of Turfus [2022], with the caveat that the mean reversion function φ r (t, u) is adjusted up (reducing its impact) by inclusion of the smile factor ψ r (t, t 1 ) in (3.7), with no impact from skew. This means that solutions based on our expansion are likely to retain better accuracy even at longer maturities than those of Turfus and Romero-Bermúdez [2021].…”
Section: Proof a Proof Of This Results Is Given Inmentioning
confidence: 97%
“…We have successfully extended the short rate model of Turfus and Romero-Bermúdez [2021] to address the pricing of SOFR/SONIA/ESTR caplets based on compounded rates. This we achieved by expressing the result as a perturbation of the analytic kernel of Turfus [2022]. The model is seen to have the following properties:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations